Multiple Transverse Colonic Perforations Associated with Slow-Release Nonsteroidal Anti-Inflammatory Drugs and Corticosteroids: A Case Report. (10th August 2011) - Shioya, Nobuki; Shibata, Shigehiro; Kojika, Masahiro; Endo, Shigeatsu
Abstract : The patient was a 36-year-old woman with sarcoidosis and Sjogren's syndrome, and had been prescribed slow-release diclofenac sodium and prednisolone for the treatment of pain associated with uveitis and erythema nodosum. She was admitted to our emergency center with abdominal pain and distention. A chest X-ray showed free air under the diaphragm on both sides, and an emergency laparotomy was performed for suspected panperitonitis associated with intestinal perforation. Laparotomy revealed several perforations on the antimesenteric aspect of the transverse colon. The resected specimen showed 11 punched-out ulcerations, many of which were up to 10 mm in diameter. The microscopic findings were non-specific, with leukocytic infiltration around the perforations. She showed good postoperative recovery, as evaluated on day 42. The present case highlights the need for exercising caution while prescribing slow-release nonsteroidal anti-inflammatory drugs with corticosteroids to patients with autoimmune diseases, as such treatment may exacerbate intestinal epithelial abnormalities.